Alveolar Echinococcosis Infection in a Monkey (Ateles geoffroyi) In Mashhad, Iran - H Borji; MR Emami; M Maleki; GH Razmi; H Kazemi Mehrjerdi; E Moghaddas (Tehran University of Medical Sciences, 2012)
Alveolar echinococcosis (AE), which is caused by ingestion of eggs of the fox tapeworm Echinococcus multilocularis, is the most potentially lethal parasitic infection because of its tendency to invade and proliferate in the liver and the difficulty in treatment. This article describes a case of alveolar echinococcosis found in Ateles geoffroyi in Mashhad, Iran. The cysts were characterized as an alveolar structure, composed of numerous small vesicles in liver, abdominal cavity, retroperitoneum and lungs. A characteristic feature of these vesicles was its exogenous tumor-like proliferation. These cysts were filled with numerous protoscoleces suggesting a potential role of this monkey in cycle of transmission. Up to now, this is probably the first report of alveolar echinococcosis in A. geoffroyi in the world.